المناخ التنظيمي وعلاقته بالرضا الوظيفي لدى العامل الجزائري - دراسة ميدانية بمصنع الإسمنت "متيجة" بمفتاح ولاية البليدة - بن خليفة, إسماعيل; فارس, علي (جامعة الوادي University of Eloued, 2014)
تهدف الدراسة الحالية إلى التعرف عن علاقة المناخ التنظيمي بالرضا الوظيفي لدى العامل الجزائري، حيث تكونت عينة الدراسة من (143) عاملاً، ولجمع المعلومات تم استخدام مقياسي المناخ التنظيمي والرضا الوظيفي، وبعد المعالجة الإحصائية أسفرت الدراسة على النتائج التالية: -توجد علاقة ارتباطية بين الهيكل التنظيمي والرضا الوظيفي لدى العامل الجزائري. -توجد علاقة ارتباطية بين القيادة والرضا الوظيفي لدى العامل الجزائري. -توجد علاقة ارتباطية بين نمط الاتصال والرضا الوظيفي لدى العامل الجزائري. - توجد علاقة ارتباطية بين المناخ التنظيمي و الرضا الوظيفي لدى العامل الجزائري The present study aims to identify the relationship of organizational climate and job satisfaction among Algerian worker, where the study sample consisted of 021 workers, and to collect data used the scale of organizational climate which prepared by Mahmoud Ayesh Taieb (2008), and a scale of job satisfaction for Mahomod Ayesh Taieb (2008), and after statistical treatment study resulted in the following results: -There is a Correlation between organizational structure and job satisfaction among Algerian worker. -There is a Correlation between leadership and job satisfaction among Algerian worker. -There is a Correlation between the pattern of communication and job satisfaction among Algerian worker. -There is a correlation between organizational climate and job satisfaction among Algerian worker.
The Relationship of Organizational Climate and Job Satisfaction among the Algerian worker
مقال- مجلة رؤى اقتصادية
Keywords: المناخ التنظيمي، الرضا الوظيفي، العامل الجزائري; organizational climate, job satisfaction, worker Algerian